Functional outcome of closed fractures of proximal humerus managed by Joshi's external stabilizing system - Gupta, Anil Kumar (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Proximal humeral fractures account for 4–5% of all fractures; most of them involving elderly and osteoporotic people. 1 51% of such fractures are displaced. Two Fractures with minimal displacement, regardless of the number of fracture lines, can be treated with closed reduction and early mobilization, but anatomical reduction in displaced fractures is difficult to obtain and the incidence of pseudarthrosis is high 3-5. We evaluated the functional results of closed Neer's 2- and 3-part proximal humerus fractures treated by Joshi's external stabilizing system. MATERIALS AND METHODS: Sixteen patients with proximal humeral fractures were managed from 2008 to 2010 by Joshi's stabilizing external fixation. They were 10 males and 6 females, with a mean age of 57.5 years. Based on Neer's classification, there were eleven 3-part fractures and five 2-part fractures. The mechanism of injuries included seven road traffic accidents and nine fall. Shoulder mobilization exercises were started within 1 week after stabilization with JESS. External fixation was removed after the evidence of union (6–8 weeks). Pain was evaluated by visual analogue scale (VAS) and shoulder range of motion was evaluated by Constant Scoring System. Followup was done at 4 weeks, 8 weeks, 12 weeks, and then at every 4 weeks. RESULTS: Mean followup was of 20.5 months (range 9-30 months). Postoperative mean VAS score and Constant Score of patients was 2.1 (±0.73) and 78.1 (±9.61) at an average followup of 6 months. Mean duration for union was 6.5 (±1.18) weeks. One case of K-wire loosening and one case of pin tract infection were the complications noted. CONCLUSION: External fixation by JESS is an alternative option to treat Neer's 2 and 3 part proximal humerus fractures with good results.